2018
DOI: 10.26905/enjourme.v2i2.1649
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary learning strategies used by first year of EFL students

Abstract: This study aims to find out the type of vocabulary learning strategies that the first year students of Faculty of Economics at Merdeka University, Pasuruan commonly use. This study used qualitative research design; that is, to analyze vocabulary learning strategies used by the students. After the students had done to fill the questionnaires, the researcher conducted one-on-one semi-structured interviews to each of the students in order to get depth information about their vocabulary learning strategies. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
2
9
0
1
Order By: Relevance
“…Secondly, the most frequently used strategies for medical students when learning general English were using an online dictionary and guessing from the context. These strategies were consistent with those seen in previous studies (Park, 2001;Rachmawati, 2018;Seddigh & Shokrpur, 2012). In this regard, Gu and Johnson (1996) observed that proficient learners make more use of guessing and dictionary strategies than other strategies.…”
Section: Ki-hosupporting
confidence: 90%
See 2 more Smart Citations
“…Secondly, the most frequently used strategies for medical students when learning general English were using an online dictionary and guessing from the context. These strategies were consistent with those seen in previous studies (Park, 2001;Rachmawati, 2018;Seddigh & Shokrpur, 2012). In this regard, Gu and Johnson (1996) observed that proficient learners make more use of guessing and dictionary strategies than other strategies.…”
Section: Ki-hosupporting
confidence: 90%
“…Furthermore, no study was found to reveal how a group of medical students would employ VLS differently when learning classmates for meaning, and guessing through textual context were the most popular strategies among Taiwanese students. Rachmawati (2018), who also modified Schmitt's (1997) classification to suit the local educational context, found that Indonesian EFL students engaged VLS by using bilingual dictionaries, guessing meaning from context, and analyzing pictures or gestures. Very recently, Laffey (2020) conducted an online experiment with 135 Korean university students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, la EAV de uso de diccionario y otras fuentes de consulta emergió como una de las más frecuentes entre las 13 categorías. Este resultado coincide con los hallazgos reportados por Asgari y Mustapha (2011), Saengpakdeejit (2014), Rachmawati (2017), Lestari y Puspitasari (2021), Shamsan et al (2021) y Alamri y Hakami (2022).…”
Section: Discusión Y Conclusionesunclassified
“…Thus, without a relative measure of vocabulary, everybody will get inconvenience in their perusing, composing, talking, and tuning in. Studies about the importance of using strategies in teaching vocabulary suggest that instead of asking students to study word lists, teacher have to provide teaching strategies to infer the unknown vocabulary (Çiftçi & Üster, 2009), thus they will remember those word in long-term memory (Rachmawati, 2018).…”
Section: Introductionmentioning
confidence: 99%